Glucose measurements in sheep using a long-term continuous glucose monitor designed for humans - dos Reis, Barbara Roqueto; Wright, Ryan K.; Thompson, Riley; Tabatabai, Nikki; Amirault, Katherine; Sujani, Sathya; White, Robin R. (Frontiers in Veterinary Science, 2024)
This study evaluated the feasibility of utilizing a continuous glucose monitors (CGM) designed for use in humans to measure glucose levels in sheep. Four Suffolk x Dorset sheep were fitted with jugular catheters and FreeStyle Libre 2 (Abbott®) glucose monitors. Glucose concentration from the CGM were compared with those from a glucometer and traditional assays during a hyperglycemic clamp, aiming to explore a broader range of physiological glucose concentrations in a controlled manner. Measurements were taken every five minutes during the infusion and every ten minutes post-infusion until baseline levels were restored. Relationships were analyzed using a linear mixed-effects model with glucometer readings as the response variables, GCM reading as fixed effects, and animal as random effect with significant level of p < 0.05. The results demonstrated a significant linear correlation between the CGM and glucometer readings both during the infusion (p = 0.0003) and afterward (p = 0.006). A glucose calorimetric test was used to confirm glucose concentrations on samples and used as gold standard. Although the glucometer and CGM did not differ from the assay method, they did differ from one another (p = 0.045). Upon more in-depth analysis, the random intercepts for animal were highly significant and one CGM showed values numerically much higher than other CGM and other glucose analysis methods. No difference among methods was observed (p = 0.715) when the outlier animal was omitted. While promising, CGM demands confirmation of initial readings and standardization against established methods before wider adoption in research or clinical applications.